An Investigation into Icelandic Whisky Production. Liquid gold from the North: Producing Icelandic whisky with Icelandic malted barley and addition of exogenous enzymes - Craig Douglas Clapcott 1979- (2021)
The aim of this study is to investigate two methods of producing fermentable wort for Icelandic whisky production, both from indigenous barley. Work of this nature is important as the spirits industry in Iceland is growing but is largely based on imported grain neutral spirit (GNS), which comes mainly from wheat grown in Europe. Iceland has an opportunity to discover its own way of producing spirits and it does not necessarily have to follow the “traditional” methods of Scotland or Ireland for example. The industry has started looking at how to protect “Íslenskt viskí” or Icelandic whisky both in Iceland and Europe (Bændablaðið, Nov 2020). Part of this process will be defining what it is and how it is to be produced, just like the Scottish had to do themselves at the beginning of the 19th century as regards their own industry by asking the question “what is whisky?” This paper aims to serve as an initial investigation into two of many potential methods that could be open to producers wishing to utilize Icelandic barley, for whisky or other spirits production. The first of these methods was to small batch malt some Icelandic barley, the second was to mash Icelandic barley solely with exogenous enzymes. Various worts were produced from these two methods and underwent basic composition analysis which will be vital in assessing suitability to spirits production. It is this author's belief that this work is needed so more Icelandic barley can be utilized for purposes other than animal feed, and to ascertain whether farmers can put their barley to more profitable use. It is hoped that work of this kind will potentially remove barriers hindering interested parties entering the Icelandic whisky and spirits industry. This author found that these two methods are suitable for potable spirits production in Iceland. The conclusion of this work is that although malting Icelandic barley is possible and has been done, it did not produce sugar levels as high as foreign malt or Icelandic barley processed at high temperatures with ...